Prevalence of overweight among youth with chronic conditions in the United States: An update from the 2016 National Survey of Children's Health. Issue 4 (30th December 2019) - Haegele, Justin A.; Foley, John T.; Healy, Sean; Paller, Alexis
Summary: Background: Surveillance of overweight trends among youth with chronic conditions can inform the prioritization of funding, research and intervention. Objectives: The primary objective of this study was to utilize the 2016 National Survey of Children's Health (NSCH) data to provide current estimates of the prevalence of overweight among US youth with common chronic conditions. A secondary purpose was to examine parental concern about weight status among youth with chronic conditions who were overweight. Methods: This study included children aged 10 to 17 years with (n=10 997) and without (n=13 408) chronic conditions from the 2016 NSCH. Estimates of overweight, and parental concern for weight status, were compared among youth with 19 common chronic conditions and youth without chronic conditions. Results: Overall, youth with chronic conditions were significantly more likely to be overweight compared with youth without chronic conditions (35.4% vs 27.8%). Overweight was most prevalent among youth with diabetes (56.4%), intellectual disabilities (53.6%) and hearing impairments (46.1%). Parents of youth with chronic conditions who were overweight were significantly more concerned that their child's weight was too high than those without chronic conditions. Conclusions: This study identifies youth with chronic conditions, particularly those with certain conditions, as being in need of prioritization of funding, research and intervention.